2023
DOI: 10.1249/mss.0000000000003143
|View full text |Cite
|
Sign up to set email alerts
|

ELABELA-APJ-Akt/YAP Signaling Axis: A Novel Mechanism of Aerobic Exercise in Cardioprotection of Myocardial Infarction Rats

Abstract: PurposeThe aim of this study was to investigate the function and mechanisms of ELABELA (ELA) in the aerobic exercise-induced antiapoptosis and angiogenesis of ischemic heart.MethodsThe myocardial infarction (MI) model of Sprague–Dawley rat was established by the ligation of the left anterior descending coronary artery. MI rats underwent 5 wk of Fc-ELA-21 subcutaneous injection and aerobic exercise training using a motorized rodent treadmill. Heart function was evaluated by hemodynamic measures. Cardiac patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Xi et al observed that aerobic training played a crucial role in inhibiting the cardiac pathological remodeling and safeguarding the myocardium in rats with myocardial infarction. Mechanically, by promoting proliferation of H9C2 cells, aerobic training kept more cardiomyocytes alive and increased angiogenesis through regulating YAP phosphorylation and nuclear translocation to activate the APJ-Akt signaling pathway [65].…”
Section: The Impact Of Physical Therapy On Disease Via Hippo/ Yap Sig...mentioning
confidence: 99%
“…Xi et al observed that aerobic training played a crucial role in inhibiting the cardiac pathological remodeling and safeguarding the myocardium in rats with myocardial infarction. Mechanically, by promoting proliferation of H9C2 cells, aerobic training kept more cardiomyocytes alive and increased angiogenesis through regulating YAP phosphorylation and nuclear translocation to activate the APJ-Akt signaling pathway [65].…”
Section: The Impact Of Physical Therapy On Disease Via Hippo/ Yap Sig...mentioning
confidence: 99%
“…Aside from the molecules mentioned above, several other compounds with anti-ferroptotic properties have demonstrated antifibrotic effects in various organs besides the lungs, and hold promise for potential therapeutic application in PF. Elabela-32 (ELA-32), an mTOR agonist, has demonstrated efficacy in mitigating myocardial infarction and attenuating myocardial fibrosis in rat models [190]. Furthermore, it has exhibited the ability to reverse TGF-β1-induced epithelial-mesenchymal transition (EMT) in human peritoneal mesothelial cells (HPMC) (123) and pulmonary vascular remodeling induced by pulmonary arterial hypertension (PAH) [191].…”
Section: Clearance Of Lipid Peroxidesmentioning
confidence: 99%